Conventional radical polymerization and iodine‐transfer polymerization of 4′‐nonafluorobutyl styrene: Surface and thermal characterizations of the resulting poly(fluorostyrene)s. Issue 15 (3rd May 2013) - Ceretta, Flavio; Zaggia, Alessandro; Conte, Lino; Ameduri, Bruno
ABSTRACT 4′‐Nonafluorobutylstyrene (3) was synthesized and polymerized by conventional and controlled radical polymerization (iodine transfer polymerization (ITP)). Such an aromatic fluoromonomer was prepared from Ullmann coupling between 1‐iodoperfluorobutane and 4‐bromoacetophenone followed by a reduction and a dehydration in 50% overall yield. Two radical polymerizations of (3) were initiated by AIBN either under conventional or controlled conditions, with 1‐iodoperfluorohexane in 84% monomer conversion and in 50% yield. ITP of (3) featured a fast monomer conversion and a linear evolution of the ln([M]0/[M]) versus time. The kinetics of radical homopolymerization of (3) enabled one to assess its square of the propagation rate to the termination rate (kp2/kt) in ITP conditions (36.2·10−2 l·mol−2·sec−2 at 80 °C) from the Tobolsky's kinetic law. Polydispersity index (Đ) of the fluoropolymer achieved by conventional polymerization was 1.30 while it worthed 1.15 when synthesized by ITP. Thermal stabilities of these oligomers were satisfactory (10% weight loss under air occurred from 305 °C) whereas the melting point was 47 °C. Contact angles and surface energies assessed from spin‐coated poly(3) films obtained by conventional (hysteresis = 18°, surface energy 18 mN.m−1) and ITP (hysteresis = 47°, surface energy 15 mN.m−1) evidenced Đ values' influence onto surface properties of the synthesized polymers. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3202–3212